The effectiveness of the RESPEK program on resilience and coping strategies among adolescents in at-risk areas in Kuala Lumpur - Abdul Ghani, Mohamad Salleh; Abd Halim, Mohd Azwan Fakhruddin; Kahar, Rojanah; Daud, Mohd Najmi; Hasbullah, Muslihah; Ahmad, Sa’odah; Wan Abdullah, Wan Arnidawati; Ashari, Asmidawati; Abdullah, Haslee Sharil Lim (Human Resources Management Academic Research Society (HRMARS), 2024)
The issue of drug abuse in Malaysia has posed a significant threat to national security. Despite various governmental efforts, it remains a challenge. One of the efforts to reduce this issue is by conducting prevention education programs, especially for high-risk groups. This study aimed to evaluate the effectiveness of a drug prevention education program called the RESPEK Program, focusing on resilience and coping strategies among adolescents in at-risk areas. Utilising a one-group pretest-posttest experimental design, the study assessed 200 adolescents from five public schools in Kuala Lumpur. The research sought to examine the effectiveness of the RESPEK program on resilience and coping strategies at the pre and post-intervention stages. The Child and Youth Resilience Measure (CYRM) and the Measure of Adolescent Coping Strategies (MACS) were used for data collection. Results indicated significant improvements in resilience and coping strategies post-intervention across all schools. These findings underscore the importance of resilience and adaptive coping strategies in preventing substance use among adolescents. The study concludes that comprehensive prevention strategies, such as the RESPEK program, are vital in addressing the multifaceted risk factors of adolescent drug abuse and highlight the need for continued efforts to build resilience and coping skills among at-risk adolescents.